A Festa do Divino de Pirenópolis/Goiás:: relações corpo-vestimenta-cidade - da Trindade Curado, João Guilherme; Caroline Lôbo, Tereza (Latitude, 2022)
The reflections depart from the triad investigated by Maia (2021): body-vestment-city, especially the transits related to dressing for the Holy do Divine. The bodies move in time and space in cities, causing interactions with and between urbanism and architecture, providing different alignments. The proposal continues punctuating Hundertwasser (RESTANY, 1987) with the five skins: the epidermis; the vestment; the man’s house; the social environment and identity, and the global environment - ecology and humanity, investigated from what is dressed during the Holy Divine Spirit Feat of Pirenópolis, an identity manifestation that allows local bodies to act in countless spaces also dressed and altered during the festivities, greatly modifying the visibilities in/of the city, correlating the material, the immaterial and the natural concerning the bodies that sew their lives. Darning the mentioned references with others in a multidisciplinary path based on bibliographical research and field experiences, perceptions about bodies, vestment and the city are attempted in festive geographic investigations, which are the purposes of this approach.